Nancy Robinson Flannery interviewed by John Farquharson - Flannery, Nancy, 1929-2011; Farquharson, John M., 1929-2016 (2002)
This interview is an update on two previous interviews conducted by Hazel de Berg in 1977 and 1980, covering the main part of her early life and career as a writer, broadcaster and publisher. In this interview Flannery recalls apects of her life in South Australia; her stint at Oxford University studying the history of architecture; her discovery of Paquita Delprat's letters to her future husband, Antarctic explorer & Professor of Geology at Adelaide University, Sir Douglas Mawson, gaining access to Mawson's replies to the letters; her work in the field of folk history, radio; her work in progress on older women, as well as the role of women today from the perspective of the traditional women.
Recorded on June 27, 2002 at Canberra, A.C.T.
Digital master available
Timed summary (2 p.) & corrected transcript (typescript, 55 leaves) available.
Keywords: Flannery, Nancy, -- 1929-2011 -- Interviews; Radio broadcasters -- South Australia -- Interviews; Authors, Australian -- South Australia -- Interviews; Editors -- South Australia -- Interviews; Broadcasters; Editors; Authors